American attack aircraft since 1926 - Johnson, E.R (McFarland & Company, 2008)
This book provides a concise historical survey of the various types of aircraft used by the United States Army Air Corps, Army Air Forces, and Air Force, and the Navy and Marine Corps to accomplish air attack missions since 1926. The text covers four types of fixed-wing aircraft: designated attack aircraft; light, medium, and tactical bombers; fighter-bombers; and adapted attack aircraft. Reports on individual aircraft types include the aircraft's original military requirements, production history, and operational record, usually accompanied by photographs, illustrations, and technical specifications. Four appendices detail aircraft designations and nomenclature used throughout the military, the organizational structure of various military air units, aircraft designs that never made it into official service, and the evolution of attack aircraft weapons and tactics.